Supportive care during pediatric hematopoietic stem cell transplantation: beyond infectious diseases. A report from workshops on supportive care of the Pediatric Diseases Working Party (PDWP) of the European Society for Blood and Marrow Transplantation (EBMT) - Nava, Tiago; Ansari, Marc; Dalle, Jean-Hugues; de Heredia, Christina Diaz; Güngör, Tayfun; Trigoso, Eugenia; Falkenberg, Ulrike; Bertaina, Alice; Gibson, Brenda; Jarisch, Andrea; Balduzzi, Adriana; Boenig, Halvard; et al. (Bone marrow transplantation, 2020)
Hematopoietic stem cell transplantation (HSCT) is currently the standard of care for many malignant and nonmalignant blood diseases. As several treatment-emerging acute toxicities are expected, optimal supportive measurements critically affect HSCT outcomes. The paucity of good clinical studies in supportive practices gives rise to the establishment of heterogeneous guidelines across the different centers, which hampers direct clinical comparison in multicentric studies. Aiming to harmonize the supportive care provided during the pediatric HSCT in Europe, the Pediatric Diseases Working Party (PDWP) of the European Society for Blood and Marrow Transplantation (EBMT) promoted dedicated workshops during the years 2017 and 2018. The present paper describes the resulting consensus on the management of sinusoidal obstructive syndrome, mucositis, enteral and parenteral nutrition, iron overload, and emesis during HSCT.
Keywords: infekční nemoci; kostní dřeň; Child; Hematopoietic Stem Cell Transplantation; Evropa; Europe; Research; dítě; transplantace hematopoetických kmenových buněk; lidé; Communicable Diseases; Humans; Bone Marrow; výzkum